2016
DOI: 10.1016/j.jtusci.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence dosimetry using natural calcite

Abstract: The TL dosimetric characteristics of the natural calcite from El Bakriya, Eastern Desert, Egypt, were studied to investigate their feasibility for use in gamma radiation dosimetry. The peak that appeared at the temperature of 283 • C on the TL glow curve was found to have a linear response to the doses over the range of 0.05-1000 Gy, especially after being annealed at 600 • C for 5 h before irradiation. Neither annealing nor irradiation changed the activation energy of the traps that produced the peak at 283 •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…[ 4 ] studied white marble samples with a TL glow curve made up of three peaks located at 180°C, 285°C and 375°C. In the study by Abdel‐Razek, [ 10 ] natural marble showed a glow curve with the same features as the calcite glow curves; three peaks were seen at 105°C, 235°C and 330°C. The particle size experiment in the first part of the study showed which particle size of the sample gave the biggest TL output, observed at the 200 μm particle size.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…[ 4 ] studied white marble samples with a TL glow curve made up of three peaks located at 180°C, 285°C and 375°C. In the study by Abdel‐Razek, [ 10 ] natural marble showed a glow curve with the same features as the calcite glow curves; three peaks were seen at 105°C, 235°C and 330°C. The particle size experiment in the first part of the study showed which particle size of the sample gave the biggest TL output, observed at the 200 μm particle size.…”
Section: Resultsmentioning
confidence: 80%
“…During preparation of the sample to make it ready for the irradiation process, the extracted marble samples were crushed using an agate mortar and washed in HCl to eliminate organic residues. [ 8–10 ] The powdered marble samples were washed with pure water several times and dried at room temperature. They were sieved using fine sieves in the range 50–400 μm and separated accordingly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid rise of TL peak intensity across the P-Tr boundary potentially records increased photoreduction of particulate Mn due to higher primary productivity and/or enhanced reduction of Mn oxides under anoxic environments. (Bruce et al, 1999;Polikreti et al, 2003;Abdel-Razek, 2016). The peak at ~170°C is likely produced by laboratory dosed phototransfer (Bruce et al, 1999;Polikreti et al, 2003).…”
Section: Increased Tl Peak Intensities and Their Implication For Primmentioning
confidence: 99%
“…Literatürde yer alan araştırmalardan da anlaşılacağı gibi TL yöntemi kullanılarak yapılan çalışmalarda doğal ya da sentetik malzemelerin radyasyon dozlarına verdikleri yanıtlar, yeniden kullanılabilirlikleri, kristal yapılarında yer alan kusurlar, bu kusurlardan kaynaklı elektron tuzakları ve bu tuzakların derinlikleri (aktivasyon enerjileri) gibi birçok özellik tespit edilebilmektedir (Rowlands ve ark., 2002;Ekdal ve ark., 2014;Rani ve Lakshmanan, 2016;Abdel-Razek 2016;Gaikwad ve ark., 2016). Benzer şekilde radyasyon çalışanlarının maruz kaldıkları radyasyon dozlarının takibinde kullanılan TLD-100 (LiF:Mg,Ti) ve TLD-800 (Li 2 B 4 O 7 :Mn) gibi termolüminesans dozimetrelerin (TLD) üretimi sırasında, bu TLD'lerin dozimetrik özelliklerine ait testler de TL yöntemi kullanılarak yapılmaktadır.…”
Section: Introductionunclassified